2011
DOI: 10.1038/onc.2011.572
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent EGFR activation induces the co-expression of IL-6 and PAI-1 via the NFkB pathway in advanced-stage epithelial ovarian cancer

Abstract: The epidermal growth factor receptor (EGFR), a member of the ErbB family of receptor tyrosine kinases, is expressed in up to 70% of epithelial ovarian cancers (EOCs), where it correlates with poor prognosis. The majority of EOCs are diagnosed at an advanced stage, and at least 50% present malignant ascites. High levels of IL-6 have been found in the ascites of EOC patients and correlate with shorter survival. Herein, we investigated the signaling cascade led by EGFR activation in EOC and assessed whether EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 35 publications
5
97
0
2
Order By: Relevance
“…signaling in the treatment of autoimmunity and cancer (21). Because EGFR activation can mediate both IL-6 production (24,25) and STAT3 activation, we investigated the role of EGFR in regulating STAT3 activation in response to IL-6.…”
mentioning
confidence: 99%
“…signaling in the treatment of autoimmunity and cancer (21). Because EGFR activation can mediate both IL-6 production (24,25) and STAT3 activation, we investigated the role of EGFR in regulating STAT3 activation in response to IL-6.…”
mentioning
confidence: 99%
“…Many studies reported that NF-kB is constitutively activated by ErbB family in breast, ovarian, prostate, and colorectal cancers (42,43). We first demonstrated that NFkB activation through 2 pathways in HCC827 and PC9 Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies displayed that NF-κB may play a vital role in transactivation of inflammatory factors, [34][35][36][37][38] we sought to further explore whether PKM2-dependent expression of CCL2 could be attributed to activation of NF-κB signaling pathway. In light of this, HT-29 and Caco-2 of CRC cells were treated with PKM2-shRNA and analyzed with western blotting for the activation of NF-κB.…”
Section: Pkm2 Interacts With P65 and Activates Nf-κb Signaling Pathwamentioning
confidence: 99%